Klasterisasi Komentar Cyberbullying Masyarakat di Instagram berdasarkan K-Means Clustering - Ramadhan, Viry Puspaning; Namung, Giasinta Mareskoti (LPPM STIKI MALANG, 2023)
Cyberbullying has become a serious problem on social media platforms like Instagram. In an effort to overcome this problem, this study aims to classify cyberbullying comments made by Instagram users. The method used in this study is K-Means Clustering, which is a grouping technique commonly used in data analysis. The comment data collected from Instagram is then analyzed using the K-Means Clustering algorithm to identify patterns and groups of similar comments. The findings from this study can provide a better understanding of the types and characteristics of cyberbullying comments that often appear on Instagram. By knowing groups of similar comments, prevention and response measures can be designed more effectively. In addition, the results of clustering can also help in the development of automatic detection algorithms to identify cyberbullying comments on social media platforms. Based on the evaluation carried out on the clustering results with a silhouette score = 0.690152, namely in cluster C1, which is a negative cluster. So, the most dominant cyberbullying comments are negative comments.